MAHMOUD KHOJA BEHBUDI'S VIEWS ON SOME JURISPRUDENTIAL ISSUES IN UZBEK PUBLICATIONS (Лучшие интеллектуальные исследования, 2025)
Annatotsiya: An active participant in the socio-economic, spiritual, educational and political processes of the Turkestan region at the beginning of the 20th century, the fact that Behbudi grew up with religious and secular knowledge from a young age was reflected in many articles written for the people in the future. At that time, he tried his best to convey the holy religion of Islam to the masses of the people.